Serological and molecular evidence of Brucella species in the rapidly growing pig sector in Kenya - Akoko, James M.; Pelle, Roger; Kivali, Velma; Schelling, E.; Shirima, G.; Machuka, Eunice M.; Mathew, C.; Fèvre, Eric M.; Kyallo, Victoria; Falzon, Laura C.; Lukambagire, A.S.; Halliday, J.E.B.; et al. (Springer, 2020)
Background Brucellosis is an emerging yet neglected zoonosis that has been reported in Kenya. Epidemiological data on brucellosis in ruminants is readily accessible; however, reports on brucellosis in pigs remain limited. This study sought to detect Brucella infection in pig serum by both serological and molecular techniques. Serum from 700 pigs randomly collected at a centralized abattoir in Nairobi region, Kenya were screened in parallel, using both Rose Bengal Test (RBT) and competitive Enzyme-Linked Immuno-sorbent Assay (cELISA) for antibodies against Brucella spp. All sera positive by RBT and 16 randomly selected negative samples were further tested using conventional PCR targeting bcsp31 gene and real-time PCR (RT-PCR) assays targeting IS711 and bcsp31 genes. Results A prevalence of 0.57% (n = 4/700) was estimated using RBT; none of these samples was positive on cELISA. All RBT positive sera were also positive by both PCRs, while two sero-negative samples also tested positive on RT-PCR (n = 6/20). Brucella abortus was detected in four out of the six PCR positive samples through a real-time multiplex PCR. Conclusion The detection of antibodies against Brucella spp. and DNA in serum from slaughterhouse pigs confirm the presence of Brucella in pigs. Therefore, investigation of the epidemiology and role of pigs in the transmission of brucellosis in Kenya is needed. Further targeted studies would be useful to systematically quantify and identify the spp. of Brucella in pigs.